2014
DOI: 10.1097/wnr.0000000000000267
|View full text |Cite
|
Sign up to set email alerts
|

Internetwork dynamic connectivity effectively differentiates schizophrenic patients from healthy controls

Abstract: Increasingly more neuroimaging studies have shown that the complex symptoms of schizophrenia are linked to disrupted neural circuits and dysconnectivity of intrinsic connectivity networks. Previous studies have assumed temporal stationarity of resting-state functional connectivity, whereas temporal dynamics have rarely been explored. Here, we utilized resting-state functional MRI with a sliding window approach to measure the amplitude of low-frequency fluctuations (ALFFs) in functional connectivity in 24 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…The dynamic property of RS functional connectivity may carry information (at least) as important as those time-averaged metrics widely explored in neuroscience studies or clinical applications, e.g., it is entirely possible that clinical populations possess disrupted dynamics, which taken together with abnormal time-averaged metrics, may offer better understanding of the associated disorders. Preliminary applications include mental disorders such as schizophrenia (Sakoglu, Pearlson et al 2010, Damaraju, Allen et al 2014, Ma, Calhoun et al 2014, Rashid, Damaraju et al 2014, Shen, Li et al 2014, Yu, Erhardt et al 2015), major depression (Allen and Cohen 2010), Alzheimer’s disease (Jones, Vemuri et al 2012), opioid analgesia (Robinson, Atlas et al 2015), temporal lobe epilepsy (Morgan, Abou-Khalil et al 2015) and childhood autism (Price, Wee et al 2014). Of note, as studies of brain dynamic functional connectivity are at quite an exploratory stage, the associated interpretations of disrupted dynamics in disorders are still very cursory – it is yet hard to identify the true mechanism from candidates such as changes in autonomic processes, vigilance states, or behavioral origins (see (Hutchison, Womelsdorf et al 2013) for a review).…”
Section: Discussionmentioning
confidence: 99%
“…The dynamic property of RS functional connectivity may carry information (at least) as important as those time-averaged metrics widely explored in neuroscience studies or clinical applications, e.g., it is entirely possible that clinical populations possess disrupted dynamics, which taken together with abnormal time-averaged metrics, may offer better understanding of the associated disorders. Preliminary applications include mental disorders such as schizophrenia (Sakoglu, Pearlson et al 2010, Damaraju, Allen et al 2014, Ma, Calhoun et al 2014, Rashid, Damaraju et al 2014, Shen, Li et al 2014, Yu, Erhardt et al 2015), major depression (Allen and Cohen 2010), Alzheimer’s disease (Jones, Vemuri et al 2012), opioid analgesia (Robinson, Atlas et al 2015), temporal lobe epilepsy (Morgan, Abou-Khalil et al 2015) and childhood autism (Price, Wee et al 2014). Of note, as studies of brain dynamic functional connectivity are at quite an exploratory stage, the associated interpretations of disrupted dynamics in disorders are still very cursory – it is yet hard to identify the true mechanism from candidates such as changes in autonomic processes, vigilance states, or behavioral origins (see (Hutchison, Womelsdorf et al 2013) for a review).…”
Section: Discussionmentioning
confidence: 99%
“…After initially removing duplicates and reviewing the titles and abstracts of the 411 relevant documents found through the search strategy, we identified 51 studies as potentially eligible for inclusion. After a detailed review of full article texts, we excluded 27 studies: 10 studies investigated fALFF differences between patients with schizophrenia and healthy controls; [43][44][45][46][47][48][49][50][51][52] 2 studies reported the dynamic ALFF differences; 53,54 2 did not cover the complete band-pass data; 55,56 5 did not use whole-brain analysis; 57-61 2 did not report whole-brain stereotactic coordinates; 28,62 4 focused on first-degree relatives; [63][64][65][66] and 2 investigated ALFF differences between patients with early-onset schizophrenia and healthy controls. 67,68 In the end, 24 studies reporting 28 data sets that investigated ALFF differences between patients with schizophrenia and healthy controls were eligible for inclusion.…”
Section: Included Studies and Sample Characteristicsmentioning
confidence: 99%
“…However, most of the aforementioned studies rely on the hypothesis that neural activity remains stationary during fMRI scanning ( Cui et al, 2019 ; Chen et al, 2020 ), while, in fact, human neural activity is dynamic and correlated to ongoing rhythmic activity over time ( Hutchison et al, 2013 ; Calhoun et al, 2014 ; Li et al, 2018 ). Recently, abnormal dynamic spontaneous neural activity has been identified in adult schizophrenia ( Shen et al, 2014 ; Hare et al, 2017 ; Zhang et al, 2019b ), but the nature of the contribution of abnormal dynamic neural activity to the onset of EOS is poorly understood.…”
Section: Introductionmentioning
confidence: 99%